S-Nitrosation of Arabidopsis thaliana Protein Tyrosine Phosphatase 1 Prevents Its Irreversible Oxidation by Hydrogen Peroxide - Nicolas-Francès, Valérie; Rossi, Jordan; Rosnoblet, Claire; Pichereaux, Carole; Hichami, Siham; Astier, Jeremy; Klinguer, Agnès; Wendehenne, David; Besson-Bard, Angélique (Frontiers in Plant Science, 2022)
Tyrosine-specific protein tyrosine phosphatases (Tyr-specific PTPases) are key signaling enzymes catalyzing the removal of the phosphate group from phosphorylated tyrosine residues on target proteins. This post-translational modification notably allows the regulation of mitogen-activated protein kinase (MAPK) cascades during defense reactions. Arabidopsis thaliana protein tyrosine phosphatase 1 (AtPTP1), the only Tyr-specific PTPase present in this plant, acts as a repressor of H2O2 production and regulates the activity of MPK3/MPK6 MAPKs by direct dephosphorylation. Here, we report that recombinant histidine (His)-AtPTP1 protein activity is directly inhibited by H2O2 and nitric oxide (NO) exogenous treatments. The effects of NO are exerted by S-nitrosation, i.e., the formation of a covalent bond between NO and a reduced cysteine residue. This post-translational modification targets the catalytic cysteine C265 and could protect the AtPTP1 protein from its irreversible oxidation by H2O2. This mechanism of protection could be a conserved mechanism in plant PTPases.